Condition of Women in Vedic Marriage Sacrament in the Himalayan Region (The Himalayan Geographers, 2023)
The marriage as a institution is deeply rooted in socio-cultural structures and is considered a significant rite of passage for humanity. The rituals have been practiced since the dawn of human civilization and have been documented in the Veda which is recognized as the oldest scriptures in the world reflecting the social structure of Vedic civilization of the Himalayan Region. The Vedas, representing the early patriarchal socio-cultural system and its rituals, provide insights into the concept of marriage as a ritual and the role of women within it. In this context, this research aims to delve into the concept of marriage as a ritual and scrutinize the position of females within the framework of Vedic marriage rituals. To achieve this objective, a historical content analysis method has been used to gather data through the hymns of Vedas and interpretations of early Indian history under the qualitative research design. The research uncovers the patriarchal nature of the Vedic context. Despite this, women are depicted as symbols of prosperity and elevation within the Vedic marriage ritual, which does not fully align with the theoretical arguments of patriarchy.